2013
DOI: 10.3126/ijasbt.v1i1.7918
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid profiling of multidrug resistant Escherichia coli strains isolated from urinary tract infection patients

Abstract: Introduction- Urinary tract infection is a common community-acquired bacterial disease. Escherichia coli is reported to be the major cause of urinary tract infection. Aim & Objective- The study was conducted with the aim of determining the antibiotic resistance pattern and plasmid profile of multidrug resistant Escherichia coli isolated from Urinary Tract Infection patients. Materials and Method- Antibiotic susceptibility tests were performed against E. coli following the protocol for the Kirby-Bauer disc diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
(19 reference statements)
4
4
0
Order By: Relevance
“…; Similarly, studies in Nigeria revealed that clinical isolates of E. coli which showed multiple drug resistance harbored plasmids with molecular sizes ranging from 2 kb to 6.5 -23 kb to a maximum of 26 kb [24,30]. In Iran, reported plasmid sizes ranged from 1 kb to 33 kb [28], similar to our results and to findings in Nepal where the 23 kb plasmid size was common [31]. We found no significant association between the presence of plasmids and drug resistance, which is in agreement with a study conducted in Nepal [31].…”
Section: Discussionsupporting
confidence: 85%
“…; Similarly, studies in Nigeria revealed that clinical isolates of E. coli which showed multiple drug resistance harbored plasmids with molecular sizes ranging from 2 kb to 6.5 -23 kb to a maximum of 26 kb [24,30]. In Iran, reported plasmid sizes ranged from 1 kb to 33 kb [28], similar to our results and to findings in Nepal where the 23 kb plasmid size was common [31]. We found no significant association between the presence of plasmids and drug resistance, which is in agreement with a study conducted in Nepal [31].…”
Section: Discussionsupporting
confidence: 85%
“…The present study observed highest number of strains of both Gram-positive and Gram-negative bacteria showed resistance to third generation cephalosporins, however the most effective antibiotics were polymixin antibiotics especially colistin and polymixin B along with tigecyclin. These findings correlate with other reports where colistin was reported as an effective drug in the treatment of infections caused by MDR bacteria [38][39].…”
Section: Discussionsupporting
confidence: 92%
“…It is of particular concern that resistance to β-lactams and fluoroquinolones is frequently driven by plasmid-borne extended spectrum β-lacatmase genes and plasmid mediated quinolone resistance (PMQR) genes in this uropathogen (Tayebi et al, 2016). Various reports suggested acquisition of plasmids of varied size and numbers associated with multiple drug resistant genes among pathogenic E. coli worldwide and nationwide (Sharma et al, 2010;Khadgi et al, 2013) with incidence of a plasmid band at 26 or 21 kb, respectively (Jan et al, 2009; et al, 2013). In this study the number and size of the clinical plasmids varied with predominance of a ∼12 kb band.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmid DNA was prepared by alkaline lysis method and electophoresed on 0.8% agarose gels and visualized by Gel documentation system (BioRad) (Khadgi et al, 2013). Plasmid bands of varied size (approximate) were detected using molecular weight marker, lambda/HindIII double digest.…”
Section: Plasmid Isolation Bacterial Conjugation and Pcr Analysismentioning
confidence: 99%